2024
DOI: 10.1039/d3ma00641g
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the conductivity of plasma polymer functionalized electrodes using gold nanoparticles

Alex Gheorghiu,
Daisy Yang,
Tiexin Li
et al.

Abstract: Plasma deposited polyoxazoline thin films (POx) are a promising solution for the rapid, scalable, and substrate-independent immuno-functionalization of electrochemical biosensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…51 To explore how the hydrophobic nature of PFO coatings could be used in such electrochemical setups, cyclic voltammetry (CV) tests were performed in which PFO coatings were deposited on a titanium foil. Since it has previously been demonstrated that AuNPs improve the charge permeability of plasma polymers, 34 no AuNP decoration of the foil was carried out here in order to study the intrinsic charge-transfer capability of the PFO film itself. Ten cycles of CV tests were performed at mild (0.2 V; −1 V) and harsh (0.2 V; −1.8 V) applied potentials on Ti substrates with 11, 23, and 68 nm thick coatings.…”
Section: Charge Transfer Through Nano Thinmentioning
confidence: 99%
See 1 more Smart Citation
“…51 To explore how the hydrophobic nature of PFO coatings could be used in such electrochemical setups, cyclic voltammetry (CV) tests were performed in which PFO coatings were deposited on a titanium foil. Since it has previously been demonstrated that AuNPs improve the charge permeability of plasma polymers, 34 no AuNP decoration of the foil was carried out here in order to study the intrinsic charge-transfer capability of the PFO film itself. Ten cycles of CV tests were performed at mild (0.2 V; −1 V) and harsh (0.2 V; −1.8 V) applied potentials on Ti substrates with 11, 23, and 68 nm thick coatings.…”
Section: Charge Transfer Through Nano Thinmentioning
confidence: 99%
“…Contrary to this common assumption, our group has shown that when deposited in thin enough layers, plasma polymers could allow charge transfer. In these works, nonfluorinated ultrathin plasma polymer coating deposited from methyloxazoline was successfully used in electrosensing applications for the detection of exosomes. , Here, we investigated ultrathin fluorinated plasma polymer films, hypothesizing that when deposited in optimally thin layers, charges will be allowed to pass through their loosely cross-linked building blocks. Such films could be very useful for electrocatalysis where a combination of hydrophobicity and charge transfer is utilized for gas conversion (CO 2 and N 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In polymer matrices, incorporating NPs significantly enhances material properties, creating advanced composite materials. , A variety of polymer-based functional materials can be prepared by selecting different types of NPs and modifying them. Oberhausen et al studied the effect of functionalized iron oxide NPs on mechanical properties; Mani et al prepared a highly sensitive and selective electrochemical sensor using magnetic NPs; Gheorghiu et al used gold NPs to enhance the electrical conductivity of the insulating substrate film; Ahmed et al employed surface-functionalized titanium dioxide NPs to improve the dielectric and thermal properties of a polyester-based varnish; Cánovas et al explored the electrochromic properties of thin films sprayed with specially treated NPs.…”
Section: Introductionmentioning
confidence: 99%